DAS02- Nasser Rabbat: Critical Encounters - AlFerzly, Michelle; Khalil, Leah; Majzoub, Raafat; Takieddine, Zena (Dongola Limited Editions; Dongola Publishing)
This publication underscores the profound connection between Rabbat's upbringing in Syria during a period of significant political transformation and his development as a critical thinker and storyteller. His journey from a reluctant choice to study architecture to becoming a prominent figure as the Director of the Aga Khan Program for Islamic Architecture at MIT illustrates his unceasing commitment to expanding the horizons of historiography, particularly within the realm of non-Western voices. "Critical Encounters: Nasser Rabbat" seeks to deepen our understanding of the urgency of history to enable the possibilities of questioning and reimagining dominant powers. Professor Rabbat's work presents a compelling account within the broader context of Arab thinkers actively reshaping their region's narrative and pushing for a more inclusive and diverse historical perspective.
English
Keywords: NA190-1555.5 History